Room temperature vulcanized oil resistant fireproof silicone rubber and preparation method thereof
Patent Information
- Application Number
- CN202610961036.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-30
- Publication Date
- 2026-10-13
AI Technical Summary
在长期接触燃油、润滑油等极性介质的工况下,油分子易扩散渗透至硅橡胶交联网络内部,对分子链产生溶胀效应,导致材料体积膨胀、力学性能显著下降,甚至引发密封失效
(1)本发明采用含硼梯形聚硅氧烷作为有机助熔剂,与传统金属氧化物助熔剂相比,不仅有效避免了金属氧化物在硅橡胶中分散性差的问题,而且在高温作用下,助熔剂发生熔融,并与有机硅热解生成的无定形二氧化硅及填料所含晶态硅酸盐之间发生界面固相反应,形成局部共熔体;该共熔体作为无机粘接相,在微观层面显著提升不同物相间的界面相容性与结合强度,进而构筑出致密、高强且结构稳定的陶瓷化骨架;该骨架在火灾工况下可长期保持结构完整性,兼具隔热防护、氧气阻隔及力学承载三重功能,显著提升硅橡胶的防火与隔热性能;
Smart Images

Figure CN122898144A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of organosilicon material technology, specifically relating to a room temperature vulcanizing oil-resistant and fire-retardant silicone rubber and its preparation method. Background Technology
[0002] Room temperature curing silicone rubber, with its excellent high and low temperature resistance, outstanding weather resistance, and good electrical insulation properties, has been widely used in aerospace, automotive, electronics, and new energy fields. In recent years, however, with increasingly stringent requirements for sealing in aerospace power systems, electric drive components of new energy vehicles, and fuel systems, the shortcomings of traditional silicone rubber in oil resistance, heat resistance, and fire resistance have become increasingly prominent. It is no longer sufficient to meet the comprehensive performance requirements of sealing materials for next-generation equipment, becoming a key technical bottleneck restricting its engineering application.
[0003] While traditional room temperature vulcanizing silicone rubber (room temperature vulcanizing) offers significant advantages such as simple construction, no need for heat curing, and in-situ molding, its molecular backbone is based on silicon-oxygen bonds, with side groups primarily consisting of non-polar groups like methyl groups. Under prolonged contact with polar media such as fuel oil and lubricating oil, oil molecules easily diffuse and penetrate into the silicone rubber's cross-linked network, causing a swelling effect on the molecular chains. This leads to material volume expansion, a significant decrease in mechanical properties, and even seal failure. Furthermore, to improve the fire resistance of silicone rubber, fluxes, fire-retardant fillers, and flame retardants are typically added. However, these fillers have poor compatibility with polysiloxane alkyl groups, severely weakening the material's tensile strength and elongation at break, and significantly reducing its adhesion to the substrate, thus affecting its suitability as a sealant in critical equipment.
[0004] Therefore, how to break the performance constraint between oil resistance and fire resistance and achieve synergistic improvement of both by molecular structure design, functional filler screening and formulation system optimization, while maintaining the ease of application of room temperature curing silicone rubber, has become a core technical challenge that urgently needs to be overcome in this field. Summary of the Invention
[0005] In view of the above-mentioned technical status, the present invention provides a room temperature vulcanizing oil-resistant and fire-retardant silicone rubber, which can not only be vulcanized at room temperature, but also improves fire resistance and adhesion.
[0006] The technical solution provided by this invention is: a room temperature vulcanizing oil-resistant and fire-retardant silicone rubber, the raw material components of which include hydroxyl-terminated polysiloxane, fire-retardant filler, flame retardant and flux; the flux is a boron-containing ladder polysiloxane; Based on parts by weight, the hydroxyl-terminated polysiloxane comprises 100 parts, the fire-retardant filler comprises 5 to 100 parts, the flame retardant comprises 5 to 100 parts, and the flux comprises 2 to 50 parts.
[0007] The present invention also provides a method for preparing the boron-containing ladder-shaped polysiloxane, comprising the following steps: (1) The organic trimekoxysilane is a trimekoxysilane containing phenyl; the organic trimekoxysilane, catalyst and mixed solvent are added to the reaction vessel, heated and stirred in a sealed manner, and low-boiling-point components are distilled off under reduced pressure, so that at least part of the alkoxy group of the organic trimekoxysilane undergoes a hydrolysis reaction to generate highly active silanol groups; The catalyst is a rare earth ternary complex, wherein rare earth ions simultaneously coordinate and bond two ligands: neodecanoate and macrocyclic Schiff base. (2) Add the boron-containing compound to the reaction vessel, heat and continue stirring to allow the hydrolyzed organic trialkoxysilane to undergo a condensation reaction with the boron-containing compound to obtain the reaction product. During the reaction, maintain reduced pressure to distill off the low-boiling-point component. (3) After cooling the reaction liquid in the reactor to room temperature, add alkane compounds and stir continuously to precipitate the reaction product. Then separate the precipitate, wash the precipitate with alkane compounds and dry it to obtain a terminal dialkylboron side-phenyl ladder polysiloxane.
[0008] As one implementation method, the preparation method of the rare earth ternary complex includes the following steps: S1: In an organic solvent-water two-phase system, saponified neodecanoic acid is mixed with an aqueous solution of rare earth inorganic salt to generate neodecanoic acid rare earth intermediate. After separation, an organic solution of neodecanoic acid rare earth intermediate is obtained. S2: Under inert gas protection, the macrocyclic Schiff base ligand is added to the organic solution of neodecanoic acid rare earth intermediate obtained in step (1), and heated under reflux to coordinate it; after the reaction is completed, the rare earth ternary complex with neodecanoic acid ion and macrocyclic Schiff base is obtained by concentration, precipitation, filtration, washing and drying.
[0009] In step S1, rare earth inorganic salts include, but are not limited to, one or more of rare earth chlorides, rare earth nitrates, and rare earth sulfates.
[0010] In step S1, the organic solvent includes, but is not limited to, one or more of toluene, xylene, tetrahydrofuran, n-hexane, cyclohexane, n-heptane, and petroleum ether.
[0011] In step S1, preferably, the molar ratio of rare earth elements to neodecanoic acid is 1.0:2.0~10.0.
[0012] In step S1, preferably, the mass ratio of water to organic solvent is 1:1.5~6.0.
[0013] In step S1, preferably, the pH of the system is controlled to be 6.0~7.5.
[0014] In step S1, preferably, the reaction temperature is 40℃~60℃.
[0015] In step S1, preferably, the reaction is stirred for 2 to 4 hours.
[0016] In step S2, preferably, the molar ratio of rare earth elements to macrocyclic Schiff base ligands is 1.0:(0.5~2.0).
[0017] In step S2, preferably, the pH of the system is controlled to be 6.0~7.5.
[0018] In step S2, preferably, the reaction temperature is 40℃~60℃.
[0019] In step S2, preferably, the reaction is stirred for 2 to 4 hours.
[0020] In step (1), the alkoxy group in the organic trimekoxysilane includes, but is not limited to, one or more of methoxy, ethoxy, propoxy, isopropoxy, butoxy, isobutoxy, long-chain alkoxy, and branched-chain alkoxy.
[0021] In step (1), the mixed solvent consists of a first solvent and a second solvent. The first solvent is toluene or xylene, and the second solvent is water and / or an alcohol compound. The alcohol compound includes, but is not limited to, one or more of methanol, ethanol, propanol, isopropanol, butanol, and isobutanol. Preferably, the mass ratio of the first solvent to the second solvent is 10:0.1 to 10:5.
[0022] In step (1), preferably, the mass of the catalyst is 0.01% to 0.1% of the mass of the organic trimekoxysilane, and more preferably 0.02% to 0.06%.
[0023] In step (1), preferably, the mass of the mixed solvent is 300% to 1000% of the mass of the organic trialkoxysilane, and more preferably 500% to 700%.
[0024] In step (1), preferably, the reaction temperature is 20℃~80℃, and more preferably 30℃~50℃.
[0025] In step (1), the reaction time is preferably 1h to 12h, and more preferably 3h to 5h.
[0026] In step (1), preferably, the stirring speed is 60 rpm to 600 rpm, and more preferably 240 rpm to 480 rpm.
[0027] In step (1), preferably, the absolute pressure during the vacuum distillation process is 1 kPa to 50 kPa, and more preferably 5 kPa to 15 kPa.
[0028] In step (2), preferably, the boron-containing compound is one or two of dialkylalkoxyborane and dialkylhydroxyborane. The alkyl group is one or two of hydrocarbon alkyl and fluoroalkyl groups, including but not limited to one or more of straight-chain alkyl, branched alkyl, and fluoroalkyl groups having 1 to 18 carbon atoms; the alkoxy group includes but is not limited to one or more of straight-chain alkoxy and branched alkoxy groups having 1 to 18 carbon atoms.
[0029] In step (2), preferably, the molar ratio of boron atoms in the boron-containing compound to silicon atoms in the organotrialkoxysilane is 1:1 to 1:20, and more preferably 1:5 to 1:12.
[0030] In step (2), preferably, the reaction temperature is 80℃~160℃, and more preferably 100℃~120℃.
[0031] In step (2), the reaction time is preferably 2h to 12h, and more preferably 4h to 7h.
[0032] In step (2), preferably, the stirring speed is 100 rpm to 300 rpm, and more preferably 120 rpm to 240 rpm.
[0033] In step (2), the absolute pressure is preferably 1 kPa to 80 kPa, and more preferably 30 kPa to 50 kPa.
[0034] In step (3), the alkane compound is a polar or nonpolar solvent, including but not limited to one or more of n-hexane, cyclohexane, n-heptane, and petroleum ether.
[0035] In step (3), preferably, the stirring speed is 200 rpm to 400 rpm.
[0036] In step (3), preferably, the stirring time is 2h to 12h.
[0037] In step (3), the method for separating the precipitate includes, but is not limited to, one or more of filtration, centrifugation, and pressure filtration.
[0038] In step (3), preferably, the molar ratio of silicon atoms to boron atoms in the target product is 1:1 to 1:20.
[0039] In step (3), preferably, the number of washing cycles is 3 to 10, and more preferably 4 to 6.
[0040] In step (3), preferably, the drying method is one or more of hot air drying, vacuum drying or microwave drying.
[0041] In step (3), preferably, the drying temperature is 50℃~200℃, and more preferably 80℃~150℃.
[0042] In step (3), preferably, the drying time is 1h to 24h, and more preferably 4h to 10h.
[0043] The hydroxyl-terminated polysiloxanes include, but are not limited to, one or a mixture of two or more of hydroxyl-terminated polydimethylsiloxane, hydroxyl-terminated polyphenylmethylsiloxane, and hydroxyl-terminated polytrifluoropropylmethylpolysiloxane.
[0044] Preferably, the kinematic viscosity of the hydroxyl-terminated polysiloxane is 1000 mPa·s to 300000 mPa·s.
[0045] Preferably, the hydroxyl-terminated polysiloxane has a hydroxyl content of 0.01% to 0.1% by mass.
[0046] The fireproof filler includes, but is not limited to, one or a mixture of two or more of the following: kaolin, attapulgite, mica powder, halloysite, mullite, vermiculite powder, silica powder, aluminum silicate, and diatomaceous earth.
[0047] Preferably, the fire-retardant filler has a particle size of 0.005~500μm.
[0048] The flame retardant includes, but is not limited to, one or a mixture of two or more of the following: platinum flame retardant, magnesium hydroxide, aluminum hydroxide, melamine, ammonium polyphosphate, melamine cyanurate, melamine pyrophosphate, and zinc borate.
[0049] Preferably, the hydroxyl-terminated polysiloxane includes at least hydroxyl-terminated trifluoropropylmethyl polysiloxane. More preferably, the hydroxyl-terminated trifluoropropylmethyl polysiloxane accounts for 10% to 90% of the mass of the hydroxyl-terminated polysiloxane. More preferably, the hydroxyl-terminated trifluoropropylmethyl polysiloxane is a hydroxyl-terminated linear trifluoropropylmethyl polysiloxane.
[0050] As one implementation, the preparation method of the hydroxyl-terminated linear trifluoropropylmethyl polysiloxane includes the following steps: T1: An alkylcyclosiloxane, a fluoroalkylcyclosiloxane, and the catalyst are added to a reaction vessel. The alkylcyclosiloxane is a cyclosiloxane containing a methyl group as a side chain, and the fluoroalkylcyclosiloxane is a cyclosiloxane containing a trifluoropropyl group as a side chain. An inert gas is introduced for protection, and the mixture is heated and stirred under anhydrous conditions. The fluoroalkylcyclosiloxane and the alkylcyclosiloxane undergo a ring-opening copolymerization reaction to form an intermediate product containing a fluoroalkyl polysiloxane. T2: Add a hydroxyl-termining agent to the reaction vessel and continue heating and stirring under anhydrous and inert gas protection. The terminating agent undergoes a condensation reaction with the intermediate product of fluorinated hydrocarbon polysiloxane, thereby terminating chain growth. At the same time, the low-boiling-point byproducts in the reaction system are distilled off under reduced pressure to obtain hydroxyl-terminated linear polytrifluoropropylmethyl polysiloxane.
[0051] In step T1, the alkylcyclosiloxanes include, but are not limited to, one or more of hexamethylcyclotrisiloxane, octamethylcyclotetrasiloxane, decamethylcyclopentasiloxane, and dodecylcyclohexasiloxane.
[0052] In step T1, preferably, some of the methyl groups on the alkylcyclosiloxane can be replaced by other groups, such as one or more groups selected from vinyl, phenyl, chlorophenyl, cyanoalkyl, ethyl, propyl, hexyl, octyl, decyl, etc.
[0053] In step T1, the fluoroalkyl cyclosiloxanes include, but are not limited to, one or more of trifluoropropylmethylcyclotrisiloxane, trifluoropropylmethylcyclotetrasiloxane, and trifluoropropylmethylcyclopentasiloxane.
[0054] In step T1, preferably, some of the methyl groups on the fluoroalkyl cyclosiloxane can be replaced by other groups, such as one or more groups selected from vinyl, phenyl, chlorophenyl, cyanoalkyl, ethyl, propyl, hexyl, octyl, decyl, etc.
[0055] In step T1, preferably, the molar content of the fluoroalkyl cyclosiloxane chain segment is 0.1% to 100%, and more preferably 30% to 60%.
[0056] In step T1, preferably, the mass of the catalyst accounts for 0.03% to 0.18% of the sum of the masses of the fluoroalkyl cyclosiloxane and the alkyl cyclosiloxane, and more preferably 0.05% to 0.12%.
[0057] In step T1, preferably, the reaction temperature is 50℃~150℃, and more preferably 80℃~120℃.
[0058] In step T1, preferably, the reaction time is 1h to 10h, and more preferably 4h to 6h.
[0059] In step T1, preferably, the stirring speed is 100 rpm to 600 rpm, and more preferably 240 rpm to 480 rpm.
[0060] In step T2, the hydroxyl end-capping agent introduces hydroxyl groups, enabling the polysiloxane to crosslink at room temperature through a condensation reaction. This includes, but is not limited to, one or more of hydroxyl silicone oil, vinyl hydroxyl silicone oil, hydroxyl-capped phenyl silicone oil, and hydroxyl-capped fluorosilicone oil.
[0061] In step T2, preferably, the molar amount of the hydroxyl end-capping agent is 0.5% to 6% of the sum of the molar amounts of fluoroalkyl cyclosiloxane and alkyl cyclosiloxane.
[0062] In step T2, preferably, the reaction temperature is 50℃~120℃, and more preferably 70℃~90℃.
[0063] In step T2, preferably, the reaction time is 2h to 8h, and more preferably 3h to 6h.
[0064] In step T2, preferably, the stirring speed is 100 rpm to 600 rpm, and more preferably 240 rpm to 480 rpm.
[0065] In step T2, preferably, the absolute pressure is 0.1 kPa to 2.0 kPa, and more preferably 0.8 kPa to 1.2 kPa.
[0066] The room temperature vulcanizing oil-resistant and fire-retardant silicone rubber may further include a diluent, which includes, but is not limited to, one or a mixture of two or more of methyl silicone oil, hydroxyl silicone oil, hydrogen-containing silicone oil, vinyl silicone oil, phenyl silicone oil, and alkoxy silicone oil. Preferably, the hydroxyl-terminated polysiloxane is expressed in parts by weight of 2 to 50 parts per 100 parts.
[0067] The room temperature vulcanizing oil-resistant and fire-retardant silicone rubber may further include a reinforcing agent, which includes, but is not limited to, one or more of fumed silica, precipitated silica, silica powder, and nano-calcium carbonate. Preferably, the specific surface area of the reinforcing agent is 10~500 m² / g. 2 / g. The hydroxyl-terminated polysiloxane is in parts by weight of 100 parts, and the reinforcing agent accounts for 5 to 100 parts by weight.
[0068] The room temperature vulcanizing oil-resistant and fire-retardant silicone rubber may further include a structure control agent. The structure control agent can increase the dispersion of the reinforcing agent in the silicone rubber and inhibit the structuring of the rubber compound. This structure control agent includes, but is not limited to, one or more mixtures of hydroxyl-terminated polydimethylsiloxane, diphenylsilanediol, dimethyldialkoxysilane, diphenyldialkoxysilane, and hexamethyldisilazane. Preferably, the amount of the structure control agent added is 0.1% to 5% of the mass of the reinforcing agent.
[0069] The room temperature vulcanizing oil-resistant and fire-retardant silicone rubber may further include a crosslinking agent, which includes, but is limited to, one or more mixtures of polyfunctional alkoxysilanes and siloxanes, acyloxysilanes, ketoxime silanes, allyloxysilanes, amide silanes and siloxanes, and aminooxysilanes and siloxanes. Preferably, the crosslinking agent accounts for 0.5 to 10 parts by mass of 100 parts of the hydroxyl-terminated polysiloxane.
[0070] The room temperature vulcanizing oil-resistant and fire-retardant silicone rubber may further include a catalyst, which includes, but is limited to, one or more mixtures of organic amines, ammonium carbamate, potassium acetate, alkali metal hydroxides, organotin compounds, titanates, guanidine alkoxysilanes, etc. Preferably, the hydroxyl-terminated polysiloxane comprises 0.01 to 3 parts by mass per 100 parts.
[0071] The room temperature vulcanizing oil-resistant and fire-retardant silicone rubber may further include a heat-resistant agent, which is one or more of the following: iron oxide, cerium oxide, magnesium oxide, titanium oxide, zinc oxide, cerium acetate, phenyl-containing polyazo compounds, indole compounds, etc. Preferably, the hydroxyl-terminated polysiloxane is present in parts per 100 parts by weight, and the heat-resistant agent accounts for 0.2 to 10 parts by weight.
[0072] The room temperature vulcanizing oil-resistant and fire-retardant silicone rubber may further include a modifier, which is used to adjust the thixotropy of the rubber compound to facilitate construction. This modifier includes, but is not limited to, one or more mixtures of cyanoalkoxysilane, liquid polybutadiene, dihydroxy polydimethylsiloxane, and polyether silicone oil. Preferably, the hydroxyl-terminated polysiloxane is present in parts per 100 parts by weight, and the heat-resistant agent comprises 0.1 to 5 parts by weight.
[0073] The room temperature vulcanizing oil-resistant and fire-retardant silicone rubber can also be an organic compound containing triazole groups. The resulting oil-resistant and fire-retardant silicone rubber not only has better mildew resistance, but also has heat resistance, UV resistance, and high flame retardancy.
[0074] The present invention also provides a method for preparing the room temperature vulcanizing oil-resistant and fire-retardant silicone rubber, comprising the following steps: The components are added to a kneader and heated to mix evenly to obtain a compound. The compound is then vulcanized at room temperature. Preferably, the compound is vulcanized at room temperature and a relative humidity of 20% to 70%. Alternatively, the compound is gradually heated under reduced pressure to remove volatile components, and then vulcanized at room temperature.
[0075] When the room temperature vulcanizing oil-resistant and fire-retardant silicone rubber component includes hydroxyl-terminated polysiloxane, diluent, structure control agent, reinforcing agent, flux, flame retardant, fire-retardant filler, heat resistant agent, crosslinking agent, catalyst, and regulator, the preparation method includes the following steps: (1) Add hydroxyl-terminated polysiloxane, diluent, structure control agent and reinforcing agent to kneader, heat and mix evenly, then gradually increase the temperature under reduced pressure and continue to knead to remove volatile components and obtain a mixture; (2) Add flux, flame retardant, fireproof filler and heat resistant agent to the kneader in step (1), heat and continue to mix, and then add to the filter press to remove solid impurities and obtain base material; (3) Add the base material, crosslinking agent, catalyst and regulator from step (2) to the planetary mixer and mix them evenly under moisture-proof conditions to obtain the compound; (4) The compound is vulcanized at room temperature to obtain silicone rubber.
[0076] In step (1), preferably, the rotor speed of the kneader is 60 rpm to 600 rpm, the mixing temperature is 40℃ to 100℃, and the time is 30 min to 360 min.
[0077] In step (1), preferably, the absolute pressure of the pressure reduction is 0.1 to 2.0 kPa, the temperature of the heating and mixing is 100°C to 200°C, and the time is 30 min to 360 min.
[0078] In step (2), preferably, the rotor speed of the kneader is 60~600 rpm, the mixing temperature is 40℃~120℃, and the time is 30 min~360 min.
[0079] In step (2), preferably, the filter screen of the filter press has a mesh size of 100-800 mesh, a barrel temperature of 40℃-120℃, and an extrusion pressure of 0.1 MPa-1.2 MPa.
[0080] In step (3), preferably, the rotor speed of the planetary mixer is 40 rpm to 300 rpm, the mixing temperature is 50℃ to 150℃, and the time is 30 min to 180 min.
[0081] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention uses boron-containing ladder polysiloxane as an organic flux. Compared with traditional metal oxide flux, it not only effectively avoids the problem of poor dispersion of metal oxide in silicone rubber, but also melts under high temperature and undergoes interfacial solid-phase reaction with amorphous silica generated by organosilicon pyrolysis and crystalline silicates contained in filler to form a local eutectic. As an inorganic binder phase, the eutectic significantly improves the interfacial compatibility and bonding strength between different phases at the micro level, thereby constructing a dense, high-strength and structurally stable ceramic skeleton. The skeleton can maintain structural integrity for a long time under fire conditions and has the triple functions of heat insulation protection, oxygen barrier and mechanical load bearing, significantly improving the fire resistance and heat insulation performance of silicone rubber. Furthermore, the boron hydroxyl groups in the boron-containing ladder polysiloxane molecular chain of this flux can form hydrogen bonds or chemical bonds with the surface active groups of substrates such as metals, ceramics, glass and plastics, and have good adhesion. Therefore, when the rubber of the present invention is coated on the surface of the substrate, it can form a strong bond with the substrate after curing at room temperature and under certain humidity, overcoming the defects of low bonding efficiency and insufficient stability of traditional oil-resistant and fire-retardant silicone rubber. In addition, by adjusting the boron content of boron-containing ladder polysiloxane, the ceramic forming temperature can be flexibly controlled to meet the needs of different working conditions.
[0082] (2) The present invention preferably uses rare earth ions as coordination centers and rare earth ternary complexes with two ligands, neodecanoate and macrocyclic Schiff base, as catalysts to catalyze the preparation of boron-containing ladder polysiloxanes. Because the rigid Schiff base skeleton "anchors" the rare earth center, and the flexible neodecanoate "regulates" the catalytic microenvironment, the long alkyl flexible chain of the neodecanoate enhances the solubility of the catalyst in organosilicon / borane mixed solvents. The rigid ring of the macrocyclic Schiff base restricts the aggregation of rare earth ions. The two ligands synergistically and precisely regulate the condensation rate of silanol-borane, inhibit random crosslinking, and directionally generate a regular double-chain ladder skeleton, so as to achieve precise synthesis of boron-containing ladder polysiloxane structure and flexible control of boron content. In addition, the catalyst has high catalytic activity, mild process conditions, and simple operation, and is suitable for large-scale and efficient preparation.
[0083] (3) The present invention preferably uses hydroxyl-terminated trifluoropropylmethyl polysiloxane as the base material, which can improve the mechanical properties and oil resistance of the silicone rubber. More preferably, hydroxyl-terminated linear trifluoropropylmethyl polysiloxane is used as the base material, which has excellent mechanical properties as well as excellent oil resistance, solvent resistance and high thermal stability, which can further improve the mechanical properties, oil resistance, solvent resistance and high thermal stability of silicone rubber.
[0084] (4) In this invention, a rare earth ternary complex with rare earth ions as coordination centers is formed in the pores of a porous solid superacid. The rare earth ions form coordination bonds with nitrogen heterocyclic carbene and acidic active components in the pores, respectively, forming a rare earth ternary complex with dual-ligand rare earth coordination units. This complex is used as a catalyst to catalyze the preparation of linear fluorinated hydrocarbon polysiloxanes. Since the active nitrogen heterocyclic carbene-rare earth center is anchored in the pores of the porous solid superacid, the solid superacid pores restrict the movement of polymer chains. That is, the movement of fluorinated hydrocarbon polysiloxanes is restricted by physical space, thereby effectively suppressing chain termination side reactions such as intramolecular "backbiting". This results in linear fluorinated hydrocarbon polysiloxanes, achieving precise control of the polymerization process. Furthermore, the rare earth ternary complex catalyst has high activity and can obtain fluorinated polysiloxanes with high polymerization degree. Therefore, it can obtain polysiloxanes with higher molecular weight and narrower molecular weight distribution. In addition, the solid nature of the catalyst makes it easy to recycle and reuse, which meets the needs of large-scale production.
[0085] (5) The silicone rubber prepared by this invention can cure at room temperature, meeting the requirements for on-site molding and construction. It also possesses excellent oil resistance, heat resistance, fire resistance, and flame retardancy, thus meeting the stringent requirements of aerospace power systems, electric drive components for new energy vehicles, and fuel system sealing. Oil resistance, fire resistance, and heat insulation... (6) The oil-resistant and fire-retardant silicone rubber of the present invention is green and environmentally friendly. It can be vulcanized at the junction of the substrate to obtain the room temperature vulcanizing type oil-resistant and fire-retardant silicone rubber of the present invention, thereby forming a firm connection with the substrate. It can also be used as a fireproof and heat-insulating material. Attached Figure Description
[0086] Figure 1 This is a photograph of the cohesive failure at the bonding interface between room temperature vulcanizing oil-resistant and fire-retardant silicone rubber and stainless steel substrate in Embodiment 1 of the present invention.
[0087] Figure 2 This is the back surface temperature distribution of the room temperature vulcanized oil-resistant and fire-retardant silicone rubber specimen during a 30-minute fire resistance test in Example 1 of this invention.
[0088] Figure 3 This is a photograph of the cohesive failure at the bonding interface between room temperature vulcanizing oil-resistant and fire-retardant silicone rubber and stainless steel substrate in Embodiment 2 of the present invention.
[0089] Figure 4 This is the back surface temperature distribution of the room temperature vulcanized oil-resistant and fire-retardant silicone rubber specimen during a 30-minute fire resistance test in Example 2 of this invention.
[0090] Figure 5 This is a photograph of the cohesive failure at the bonding interface between room temperature vulcanizing oil-resistant and fire-retardant silicone rubber and stainless steel substrate in Embodiment 3 of the present invention.
[0091] Figure 6This is the back surface temperature distribution of the room temperature vulcanized oil-resistant and fire-retardant silicone rubber specimen during a 30-minute fire resistance test in Example 3 of this invention. Detailed Implementation
[0092] The present invention will be further described in detail below with reference to the embodiments. It should be noted that the embodiments described below are intended to facilitate the understanding of the present invention and do not limit it in any way.
[0093] Example 1: By weight, room temperature vulcanizing oil-resistant and fire-retardant silicone rubber consists of the following components: 60 parts of hydroxyl-terminated trifluoropropylmethyl polysiloxane with a viscosity of 6000 mPa·s 40 parts of hydroxyl-terminated polyphenylmethylsiloxane with a viscosity of 4000 mPa·s Five parts of phenylmethyl silicone oil with a viscosity of 200 mPa·s Five parts of trifluoropropylmethyl silicone oil with a viscosity of 200 mPa·s 16 parts of a terminally trifluoropropylboron-terminated phenyl ladder-shaped polysiloxane with a silicon-to-boron molar ratio of 4.8:1. Specific surface area 300m 2 12 parts of fumed silica (g / g) 1.2 parts of hexamethyldisilazane 34 parts of magnesium hydroxide, 0.5 parts platinum flame retardant 18 portions of halloysite with a particle size of 50 μm, Vinyltrimethoxysilane 4.5 parts, 0.9 parts of tetrabutyl titanate, 1.2 parts of nano-cerium oxide, 0.8 parts of liquid polybutadiene 0.3 parts of benzotriazole.
[0094] The preparation method of hydroxyl-terminated trifluoropropylmethyl polysiloxane is as follows: (1) 1086g of hexamethylcyclotrisiloxane, 2082g of methyltrifluoropropylcyclopentasiloxane and 3.1g of catalyst were added to a 20L reactor and stirred for 3h under anhydrous and nitrogen protection at 95°C.
[0095] The catalyst is a rare-earth ternary complex of nitrogen heterocyclic carbene / cerium / phosphate, which is constructed from cerium ions, nitrogen heterocyclic carbene, and sulfate, an acidic active component supported within the pores of porous phosphate / alumina fiber solid superacid. Within these pores, cerium ions simultaneously coordinate and bond with both the nitrogen heterocyclic carbene and the acidic active component phosphate. The porous phosphate / alumina fiber solid superacid accounts for 95.5% of the mass of the rare-earth ternary complex; the molar ratio of nitrogen heterocyclic carbene to rare-earth elements is 0.98:1.
[0096] The preparation method of this rare earth ternary complex is as follows: The aminothiazolylbenzimidazole bromide in the specified ratio was dissolved in anhydrous toluene. A porous sulfate / titanium dioxide solid superacid, activated by baking at 500°C for 3 hours, was added. The mixture was stirred at room temperature to allow the aminothiazolylbenzimidazole bromide to fully impregnate and adsorb within the pores of the sulfate / titanium dioxide solid superacid. The reaction system was cooled to -4°C, and anhydrous toluene solution of aminothiazolylbenzimidazole bromide was slowly added dropwise with continuous stirring. After the addition was complete, the reaction was continued at -4°C for 1.2 hours, then slowly raised to room temperature and continued for 8 hours. After the reaction was complete, the precipitate was separated by centrifugation, washed twice with anhydrous n-hexane, and dried under vacuum at room temperature to obtain the rare earth ternary complex.
[0097] (2) Add 43.2g of ethanol end-capping agent to the above reaction vessel, and continue to stir the reaction for 2.4h under anhydrous and nitrogen protection at 95°C. After the reaction is completed, raise the temperature to 195°C and reduce the pressure to 1.7kPa to distill off unreacted residues and low-boiling-point byproducts to obtain hydroxyl-terminated trifluoropropylmethyl polysiloxane with a viscosity of 6000mPa·s.
[0098] The preparation method of the terminal trifluoropropyl boron-terminated side-phenyl ladder polysiloxane is as follows: (1) Take 1620g of phenyltriethoxysilane, 3.1 The catalyst and a mixture of 4100g xylene and ethanol in a mass ratio of 10:1 were sequentially added to a 20L vacuum reactor. The reactor was sealed and reacted for 4 hours at a heating temperature of 45℃, a stirring speed of 360rpm, and an absolute pressure of 1.6kPa, and low-boiling-point byproducts were distilled off.
[0099] The catalyst is a rare earth lanthanum ternary complex, which is a ternary complex in which rare earth lanthanum ions are simultaneously coordinated and bonded to two ligands: neodecanoate and dodecaza macrocyclic Schiff base.
[0100] The preparation method of this rare earth lanthanum ternary complex is as follows: S1: In a toluene-water two-phase system, neodecanoic acid treated with sodium hydroxide saponification was mixed with an aqueous solution of the rare earth inorganic salt lanthanum chloride. The two reacted to form a rare earth lanthanum neodecanoate intermediate. After separation, a toluene solution of the rare earth lanthanum neodecanoate intermediate was obtained. The molar ratio of the rare earth inorganic salt lanthanum chloride to ammonium neodecanoate was 1.0:2.1; the reaction temperature was controlled at 45℃, and the reaction was stirred for 1.8 h; the mass ratio of water to toluene was 1:8.95.
[0101] S2: Under inert gas protection, the dodecaza-macrocyclic Schiff base ligand was added to the toluene solution of the neodecanoic acid rare earth lanthanum intermediate from step S1, and heated to reflux to allow for complete coordination. After the reaction was completed, the mixture was concentrated, precipitated, filtered, washed, and dried to obtain a rare earth lanthanum ternary complex simultaneously coordinated with both neodecanoic acid and the dodecaza-macrocyclic Schiff base. The molar ratio of the rare earth inorganic salt lanthanum chloride to the dodecaza-macrocyclic Schiff base ligand was 1.0:1.18. The reaction temperature was controlled at 55℃, and the reaction was stirred for 2.5 h.
[0102] (2) Add 172g of trifluoropropyl methoxyborane to the vacuum reactor, and react in a closed container for 5.5h at a heating temperature of 95℃, a stirring speed of 240rpm and an absolute pressure of 1.15kPa, and distill off the low-boiling-point byproduct.
[0103] (3) Cool the reaction liquid in the vacuum reactor to room temperature, then add 1790 mL of n-hexane to the reactor and stir continuously at 180 rpm for 1.2 h to gradually precipitate the reaction product; then, vacuum filter the precipitated reaction product and wash it 6 times with 5800 mL of petroleum ether, and then dry it in a forced-air oven at 125 °C for 5 h to obtain the terminal trifluoropropyl boron side phenyl ladder polysiloxane.
[0104] The preparation method of the above-mentioned room temperature vulcanizing oil-resistant and fire-retardant silicone rubber includes the following steps: (1) Hydroxyl-terminated trifluoropropylmethyl polysiloxane, hydroxyl-terminated polyphenylmethyl siloxane, phenylmethyl silicone oil, trifluoropropylmethyl silicone oil, fumed silica and hexamethyldisilazane were added to a 10L kneader in sequence and kneaded for 3 hours at a rotor speed of 200 rpm and a temperature of 65°C. Then the pressure was reduced to 0.5 kPa and the temperature was gradually increased to 150°C. Kneading was continued for 2 hours to remove low-boiling-point substances such as ammonia. (2) The terminal trifluoropropyl boron side phenyl ladder polysiloxane, magnesium hydroxide, halloysite, nano cerium oxide, benzotriazole and platinum flame retardant were added to the above kneader in sequence and continued to be mixed for 3 hours at a rotor speed of 200 rpm and a temperature of 85°C. Then it was added to a plunger filter with a barrel temperature of 50°C and an extrusion pressure of 0.3 MPa and filtered through a 300-mesh filter to remove impurities and obtain pure base material. (3) The above base material, vinyltrimethoxysilane, and tetrabutyl titanate liquid polybutadiene are added to a 10L planetary mixer in sequence and mixed in a moisture-proof manner at a rotor speed of 180rpm and a temperature of 80℃ for 3 hours to obtain the compound.
[0105] The prepared rubber compound was filled into a polytetrafluoroethylene plastic mold and vulcanized for 7 days at 25°C and 55% relative humidity to obtain a rubber test piece with a thickness of 3 mm. The test piece was then subjected to tests on mechanical properties, flame retardancy, oil resistance, high and low temperature resistance, and fire resistance.
[0106] Table 1: Performance testing methods and results of the test specimens in Example 1
[0107] Meanwhile, the prepared compound was coated between two stainless steel plates, glass plates, or chlorinated polyethylene plates to form shear bond specimens with an overlap area of 10 mm × 200 mm and an adhesive layer thickness of 10 mm. After curing at 20°C and 55% relative humidity for 7 days, the shear bond strength was tested. The shear bond strength tests with stainless steel and glass substrates showed cohesive failure characteristics, indicating that the silicone rubber formed a strong chemical bond with these substrates, with bond strength superior to bulk strength and excellent interfacial bonding reliability. Figure 1 shows a photograph of the cohesive failure at the interface with the stainless steel substrate.
[0108] In addition, the 3mm thick specimen was subjected to continuous burning under a butane torch flame at 1300℃ for 30 minutes, and the cracking and temperature distribution on the back side were recorded. The test results are as follows: Figure 2 As shown, a dense, complete, and crack-free porous ceramic layer can be rapidly formed on the surface of the test piece. This ceramic layer can effectively block the flame propagation path and significantly reduce the heat conduction efficiency, so that the temperature of the center of the back side of the test piece is always maintained below 52°C throughout the entire burning process.
[0109] Example 2: By weight, room temperature vulcanizing oil-resistant and fire-retardant silicone rubber consists of the following components: 65 parts of hydroxyl-terminated trifluoropropylmethyl polysiloxane with a viscosity of 11000 mPa·s 35 parts of hydroxyl-terminated polydimethylsiloxane with a viscosity of 9500 mPa·s 12 parts of dimethyl silicone oil with a viscosity of 800 mPa·s 18 parts of a silicon-boron molar ratio of 5:1 with terminal diethylboron and side-phenyl ladder-shaped polysiloxane. Specific surface area 200m² 2 17 parts of precipitated silica per g 1.7 parts of diphenylsilanediol, 20 parts aluminum hydroxide 18 parts of zinc borate, 14 parts of vermiculite powder with a particle size of 35μm. 8 parts of methyl tributanone oxime silane 0.2 parts of dibutyltin dilaurate, 1.8 parts of nano-iron oxide, 1.1 parts polyether silicone oil, 0.6 parts of 2-phenylbenzotriazole.
[0110] The preparation method of hydroxyl-terminated trifluoropropylmethyl polysiloxane is as follows: (1) 1086g of hexamethylcyclotrisiloxane, 2082g of methyltrifluoropropylcyclopentasiloxane and 4.7g of catalyst were added to a 20L reactor and stirred for 3h under anhydrous and nitrogen protection at 95°C.
[0111] 1,3-Bis(2,4,6-trimethylphenyl)imidazolium chloride / yttrium / persulfate
[0112] The catalyst is a rare-earth ternary complex of nitrogen heterocyclic carbene / yttrium / fluoroantimonyic acid, which is constructed from yttrium ions, nitrogen heterocyclic carbene, and sulfate ions, an acidic active component supported in porous persulfate / zeolite solid superacid channels. Within these channels, yttrium ions simultaneously coordinate and bond with both the nitrogen heterocyclic carbene and the acidic active component fluoroantimonyic acid. The porous fluoroantimonyic acid / zeolite solid superacid accounts for 93.8% of the mass of the rare-earth ternary complex; the molar ratio of nitrogen heterocyclic carbene to rare-earth elements is 1.18:1.
[0113] The preparation method of this rare earth ternary complex is as follows: The 1,3-bis(2,4,6-trimethylphenyl)imidazolium chloride solution was dissolved in anhydrous toluene. A porous fluoroantimony acid / zeolite solid superacid, activated by calcination at 500°C for 3 hours, was added. The mixture was stirred at room temperature to allow the 1,3-bis(2,4,6-trimethylphenyl)imidazolium chloride to be fully impregnated and adsorbed within the pores of the fluoroantimony acid / zeolite solid superacid. The reaction system was cooled to -2°C, and an anhydrous toluene solution of 1,3-bis(2,4,6-trimethylphenyl)imidazolium chloride was slowly added dropwise with continuous stirring. After the addition was complete, the reaction was continued at -2°C for 1.5 hours, then slowly raised to room temperature and continued for 8 hours. After the reaction was complete, the precipitate was separated by centrifugation, washed twice with anhydrous n-hexane, and dried under vacuum at room temperature to obtain the rare earth ternary complex.
[0114] (2) Add 43.2g of ethanol end-capping agent to the above reaction vessel, and continue to stir the reaction for 2h under anhydrous and nitrogen protection at 95°C. After the reaction is completed, raise the temperature to 210°C and reduce the pressure to 1.6kPa to distill off the unreacted residue and low-boiling-point byproducts to obtain hydroxyl-terminated trifluoropropylmethyl polysiloxane with a viscosity of 6000mPa·s.
[0115] The preparation method of the terminal diethylboron-terminated phenyl ladder polysiloxane is as follows: (1) 1000g of phenyltrimethoxysilane, 3.4g of catalyst, and 4100g of a mixture of toluene and water in a mass ratio of 44:5 were added sequentially to a 10L vacuum reactor. The reactor was sealed and reacted for 2h at a heating temperature of 25℃, a stirring speed of 200rpm, and an absolute pressure of 1.2kPa. Low-boiling-point byproducts were distilled off.
[0116] The catalyst is a rare earth yttrium ternary complex, which is a ternary complex in which rare earth yttrium ions are simultaneously coordinated and bonded to two ligands: neodecanoate and a thioheteroatom macrocyclic Schiff base.
[0117] The preparation method of this rare earth yttrium ternary complex is as follows: S1: In a toluene-water two-phase system, neodecanoic acid treated with sodium hydroxide saponification is mixed with an aqueous solution of the rare earth inorganic salt yttrium nitrate. The two react to form a neodecanoic acid-rare earth yttrium intermediate. After separation, a toluene solution of the neodecanoic acid-rare earth yttrium intermediate is obtained. The molar ratio of the rare earth inorganic salt yttrium nitrate to sodium neodecanoate is... 1.0:3.6 The reaction temperature was controlled at 40℃, and the reaction was stirred for 3 hours; the mass ratio of water to toluene was 1:9.5.
[0118] S2: Under inert gas protection, the sulfide-heteroatom macrocyclic Schiff base ligand was added to the toluene solution of the neodecanoic acid rare earth yttrium intermediate from step S1, and heated to reflux to allow for complete coordination. After the reaction was completed, the mixture was concentrated, precipitated, filtered, washed, and dried to obtain a rare earth yttrium ternary complex simultaneously coordinated and bonded to both neodecanoic acid and the sulfide-heteroatom macrocyclic Schiff base. The molar ratio of the rare earth inorganic salt yttrium nitrate to the sulfide-heteroatom macrocyclic Schiff base ligand was 1.0:1.45. The reaction temperature was controlled at 55℃, and the reaction was stirred for 2.4 h.
[0119] (2) Add 134g of dimethylethoxyborane to the vacuum reactor and react in a closed container for 7.5h at a heating temperature of 85℃, a stirring speed of 360rpm and an absolute pressure of 1.3kPa, and distill off the low-boiling-point byproduct.
[0120] (3) Cool the reaction liquid in the vacuum reactor to room temperature, then add 1200 mL of hexane to the reactor and stir continuously at 360 rpm for 1.4 h to gradually precipitate the reaction product; then, vacuum filter the precipitated reaction product and wash it 6 times with 3400 mL of tetrahydrofuran, and then dry it in a forced-air oven at 105 °C for 6 h to obtain a terminal dimethylboron side-phenyl ladder polysiloxane.
[0121] The preparation method of the above-mentioned room temperature vulcanizing oil-resistant and fire-retardant silicone rubber includes the following steps: (1) Hydroxyl-terminated trifluoropropylmethyl polysiloxane, hydroxyl-terminated polydimethylsiloxane, dimethyl silicone oil, precipitated silica and diphenylsilanediol were added to a 20L kneader in sequence and kneaded for 4 hours at a rotor speed of 300 rpm and a temperature of 50°C. Then the pressure was reduced to 1.0 kPa and the temperature was gradually increased to 165°C. Kneading was continued for 3 hours to remove low-boiling-point substances such as alcohols.
[0122] (2) The terminal dimethylboron-terminated phenyl ladder polysiloxane, aluminum hydroxide, zinc borate, vermiculite powder, nano iron oxide, and 2-phenylbenzotriazole were added to the above kneader in sequence and mixed for 4 hours at a rotor speed of 300 rpm and a temperature of 60°C. Then, the mixture was added to a plunger-type filter press with a barrel temperature of 40°C and an extrusion pressure of 0.15 MPa and filtered through a 400-mesh filter screen to remove impurities and obtain pure base material.
[0123] (3) The above base material, methyl tributanone oxime silane, dibutyltin dilaurate and polyether silicone oil are added to a 20L planetary mixer in sequence and mixed in a moisture-proof manner at a rotor speed of 210rpm and a temperature of 65℃ for 3.5h to obtain the compound.
[0124] The above-prepared compound was filled into a polytetrafluoroethylene plastic mold and vulcanized for 7 days at 25°C and 55% relative humidity to obtain a rubber test piece with a thickness of 3 mm. The test piece was tested for mechanical, flame retardant, oil resistance, high and low temperature resistance, and fire resistance properties. The results are shown in Table 2 below.
[0125] Table 2: Performance testing methods and results of the test pieces in Example 2
[0126] Meanwhile, the prepared compound was coated between two stainless steel plates, a glass plate, and a polycarbonate plate to form shear bond specimens with an overlap area of 10 mm × 200 mm and an adhesive layer thickness of 10 mm. After curing at 20°C and 55% relative humidity for 7 days, the shear bond strength was tested. The shear bond strength tests with stainless steel and glass substrates showed cohesive failure characteristics, indicating that the silicone rubber formed a strong chemical bond with these substrates, with bond strength superior to bulk strength and excellent interfacial bonding reliability. Figure 3 shows a photograph of the cohesive failure at the interface with the stainless steel substrate.
[0127] In addition, the 3 mm thick specimen was subjected to a butane torch flame at 1300 ℃ for 30 minutes, and the cracking and temperature distribution on the back side were recorded. The test results are as follows: Figure 4 As shown, a dense, complete, and crack-free porous ceramic layer can be rapidly formed on the surface of the test piece. This ceramic layer can effectively block the flame propagation path and significantly reduce the heat conduction efficiency, so that the temperature of the center of the back side of the test piece is always maintained below 50°C throughout the entire burning process.
[0128] Example 3: By weight, room temperature curing oil-resistant and fire-retardant silicone rubber consists of the following components: 54 parts of hydroxyl-terminated trifluoropropyl ethyl polysiloxane with a viscosity of 24000 mPa·s. 46 parts of hydroxyl-terminated polyethylmethylsiloxane with a viscosity of 24000 mPa·s 26 parts of trifluoropropyl ethyl silicone oil with a viscosity of 1200 mPa·s 16 parts of a side-phenyl ladder-shaped polysiloxane with a silicon-to-boron molar ratio of 6.2:1 and terminal diethylboron. Specific surface area 350m² 2 14 parts of fumed silica (g / g) Specific surface area 800m² 2 8 parts of nano-calcium phosphate per gram 2.4 parts of diphenyldimethoxysilane, 32 parts magnesium hydroxide, 6 parts of ammonium polyphosphate Six parts of aluminum silicate with a particle size of 35 μm. Nine portions of diatomaceous earth with a particle size of 20 μm. 9.5 parts of ethyltriacetoxysilane 1.1 parts of tetraisopropyl titanate, 2.6 parts of nano-titanium oxide, 1.7 parts of cyanoethoxysilane, 0.45 parts of methylbenzotriazole.
[0129] The preparation method of hydroxyl-terminated trifluoropropylmethyl polysiloxane is as follows: (1) 968g of octamethylcyclotetrasiloxane, 1900g of trifluoropropylethylcyclotrisiloxane and 3.9g of catalyst were added to a 20L reactor and stirred for 4.8h under anhydrous and nitrogen protection at 85°C.
[0130] 1,3-Bis(2,6-diisopropylphenyl)imidazolium-2-carboxylate / ytterbium / silicotungstic acid
[0131] The catalyst is a rare-earth ternary complex of nitrogen-heterocyclic carbene / ytterbium / silicotungstic acid, which is constructed from ytterbium ions, nitrogen-heterocyclic carbene, and sulfate ions, an acidic active component supported within the pores of porous silicotungstic acid / porous carbon fiber solid superacid. Within these pores, ytterbium ions simultaneously coordinate and bond with both the nitrogen-heterocyclic carbene and the acidic active component silicotungstic acid. The porous silicotungstic acid / porous carbon fiber solid superacid accounts for 89.3% of the total mass of the rare-earth ternary complex; the molar ratio of nitrogen-heterocyclic carbene to rare-earth elements is 0.76:1.
[0132] The preparation method of this rare earth ternary complex is as follows: The 1,3-bis(2,6-diisopropylphenyl)imidazolium-2-carboxylate of the specified ratio was dissolved in anhydrous toluene. A porous silicotungstic acid / porous carbon fiber solid superacid, activated by baking at 435°C for 4.6 h, was added. The mixture was stirred at room temperature to allow the 1,3-bis(2,6-diisopropylphenyl)imidazolium-2-carboxylate to be fully impregnated and adsorbed within the pores of the silicotungstic acid / porous carbon fiber solid superacid. The reaction system was cooled to -4°C, and an anhydrous toluene solution of tris(trimethylsilylaniline)ytterbium was slowly added dropwise with continuous stirring. After the addition was complete, the reaction was continued at -4°C for 2.2 h, then slowly raised to room temperature and continued for 9.5 h. After the reaction was complete, the precipitate was separated by centrifugation, washed three times with anhydrous petroleum ether, and dried under vacuum at room temperature to obtain the rare earth ternary complex.
[0133] (2) Add 36.5g of hydroxyl-terminated fluorosilicone oil with a viscosity of 180mPa·s to the above reaction vessel. Continue stirring and reacting for 1.8h under anhydrous and nitrogen protection at 105℃. After the reaction is completed, raise the temperature to 195℃ and reduce the pressure to 1.4kPa to distill off unreacted residues and low-boiling-point byproducts to obtain hydroxyl-terminated trifluoropropyl ethyl polysiloxane with a viscosity of 24000mPa·s.
[0134] The preparation method of the terminal dimethylboron-terminated phenyl ladder polysiloxane is as follows: (1) 980g of phenyltripropoxysilane, 2.9g of catalyst, and 3960g of a mixture of toluene and propanol in a mass ratio of 10:2.8 were added to a 10L vacuum reactor. The reactor was sealed and reacted for 1.8h at a heating temperature of 35℃, a stirring speed of 240rpm, and an absolute pressure of 1.6kPa. Low-boiling-point byproducts were distilled off.
[0135] The catalyst is a rare earth neodymium ternary complex, which is a ternary complex in which rare earth neodymium ions are simultaneously coordinated and bonded to two ligands: neodecanoate and tetraaza macrocyclic Schiff base.
[0136] The preparation method of this rare earth yttrium ternary complex is as follows: S1: In a toluene-water two-phase system, neodecanoic acid treated with ammonia saponification was mixed with an aqueous solution of neodymium sulfate, a rare earth inorganic salt. The two reacted to generate a neodecanoic acid rare earth neodymium intermediate. After separation, a toluene solution of the neodecanoic acid rare earth neodymium intermediate was obtained. The molar ratio of neodymium sulfate to sodium neodecanoate was 1.0:2.3; the reaction temperature was controlled at 55℃, and the reaction was stirred for 4 hours; the mass ratio of water to xylene was 1:5.5.
[0137] S2: Under inert gas protection, the tetraaza-macrocyclic Schiff base ligand was added to the toluene solution of the neodecanoic acid rare earth neodymium intermediate from step S1, and heated to reflux to allow for complete coordination. After the reaction was completed, the mixture was concentrated, precipitated, filtered, washed, and dried to obtain a rare earth neodymium ternary complex simultaneously coordinated and bonded to both neodecanoic acid and the tetraaza-macrocyclic Schiff base. The molar ratio of the rare earth inorganic salt neodymium yttrium sulfate to the tetraaza-macrocyclic Schiff base ligand was 1.0:1.12. The reaction temperature was controlled at 65℃, and the reaction was stirred for 3.5 h.
[0138] (2) Add 118g of diethylhydroxyborane to the vacuum reactor, and react in a closed container for 8h at a heating temperature of 80℃, a stirring speed of 300rpm and an absolute pressure of 1.2kPa to distill off low-boiling-point byproducts.
[0139] (3) Cool the reaction liquid in the vacuum reactor to room temperature, then add 1450 mL of cyclohexane to the reactor and stir continuously at 300 rpm for 1 h to gradually precipitate the reaction product; then, vacuum filter the precipitated reaction product and wash it 6 times with 3000 mL of tetrahydrofuran, and then dry it in a forced-air oven at 120 °C for 5 h to obtain a terminal diethylboron side-phenyl ladder polysiloxane.
[0140] The preparation method of the above-mentioned room temperature curing oil-resistant and fire-retardant silicone rubber includes the following steps: (1) Hydroxyl-terminated trifluoropropyl ethyl polysiloxane, hydroxyl-terminated polyethyl methyl siloxane, trifluoropropyl ethyl silicone oil, fumed silica, nano calcium calcate, and diphenyl dimethoxysilane were sequentially added to a 20L kneader and kneaded for 6 hours at a rotor speed of 240 rpm and a temperature of 60°C. Then the pressure was reduced to 1.2 kPa and the temperature was gradually increased to 170°C. The kneading continued for 2.5 hours to remove low-boiling-point substances such as alcohols.
[0141] (2) Diethylboron side-phenyl ladder polysiloxane, magnesium hydroxide, ammonium polyphosphate, aluminum silicate, diatomaceous earth, nano titanium dioxide and methylbenzotriazole were added to the above kneader in sequence and kneaded for 3.5 hours at a rotor speed of 340 rpm and a temperature of 80 ℃. Then the mixture was added to a plunger filter with a barrel temperature of 50 ℃ and an extrusion pressure of 0.20 MPa and filtered through a 600-mesh filter to remove impurities and obtain pure base material.
[0142] (3) The above base material, ethyltriacetoxysilane, tetraisopropyl titanate and cyanoethoxysilane are added to a 20L planetary mixer in sequence and mixed in a moisture-proof manner at a rotor speed of 240rpm and a temperature of 80℃ for 4h to obtain the compound.
[0143] The above-prepared compound was filled into a polytetrafluoroethylene plastic mold and vulcanized for 7 days at 25°C and 55% relative humidity to obtain a rubber test piece with a thickness of 3 mm. The test piece was tested for mechanical, flame retardant, oil resistance, high and low temperature resistance, and fire resistance properties. The results are shown in Table 3 below.
[0144] Table 3: Performance testing methods and results of the test pieces in Example 3
[0145] Meanwhile, the prepared compound was used to prepare shear bond specimens coated on the surfaces of two stainless steel plates, a glass plate, and a polycarbonate plate, respectively. The overlap area was 10 mm × 200 mm, and the adhesive layer thickness was 10 mm. After curing at 20°C and 55% relative humidity for 7 days, the shear bond strength was tested. The shear bond strength tests with stainless steel and glass substrates showed cohesive failure characteristics, indicating that the silicone rubber formed a strong chemical bond with these substrates, with bond strength superior to bulk strength and excellent interfacial bonding reliability. Figure 5 shows a photograph of the cohesive failure at the interface with the stainless steel substrate.
[0146] In addition, the 3mm thick specimen was subjected to continuous burning under a butane torch flame at 1300℃ for 30 minutes, and the cracking and temperature distribution on the back side were recorded. The test results are as follows: Figure 6As shown, a dense, complete, and crack-free porous ceramic layer can be rapidly formed on the surface of the test piece. This ceramic layer can effectively block the flame propagation path and significantly reduce the heat conduction efficiency, so that the temperature of the center of the back side of the test piece is always maintained below 53°C throughout the entire burning process.
[0147] The above embodiments provide a detailed description of the technical solution of the present invention. It should be understood that the above descriptions are only specific embodiments of the present invention and are not intended to limit the present invention. Any modifications, additions, or similar substitutions made within the scope of the principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A room temperature vulcanizing, oil-resistant, fire-retardant silicone rubber, characterized in that: The raw material components include hydroxyl-terminated polysiloxane, fire-retardant filler, flame retardant and flux; the flux is a boron-containing ladder-shaped polysiloxane. Based on parts by weight, the hydroxyl-terminated polysiloxane comprises 100 parts, the fire-retardant filler comprises 5 to 100 parts, the flame retardant comprises 5 to 100 parts, and the flux comprises 2 to 50 parts.
2. The room temperature vulcanizing oil-resistant and fire-retardant silicone rubber as described in claim 1, characterized in that: The method for preparing the boron-containing ladder-shaped polysiloxane includes the following steps: (1) The organic trimekoxysilane is a trimekoxysilane containing phenyl; the organic trimekoxysilane, catalyst and mixed solvent are added to the reaction vessel, heated and stirred in a sealed manner, and low-boiling-point components are distilled off under reduced pressure, so that at least part of the alkoxy group of the organic trimekoxysilane undergoes a hydrolysis reaction to generate highly active silanol groups; The catalyst is a rare earth ternary complex, wherein rare earth ions simultaneously coordinate and bond two ligands: neodecanoate and macrocyclic Schiff base. (2) Add the boron-containing compound to the reaction vessel, heat and continue stirring to allow the hydrolyzed organic trialkoxysilane to undergo a condensation reaction with the boron-containing compound to obtain the reaction product. During the reaction, maintain reduced pressure to distill off the low-boiling-point component. (3) After cooling the reaction liquid in the reactor to room temperature, add alkane compounds and stir continuously to precipitate the reaction product. Then separate the precipitate, wash the precipitate with alkane compounds and dry it to obtain a terminal dialkylboron side-phenyl ladder polysiloxane.
3. The room temperature vulcanizing oil-resistant and fire-retardant silicone rubber as described in claim 2, characterized in that: The preparation method of the rare earth ternary complex includes the following steps: S1: In an organic solvent-water two-phase system, saponified neodecanoic acid is mixed with an aqueous solution of rare earth inorganic salt to generate neodecanoic acid rare earth intermediate. After separation, an organic solution of neodecanoic acid rare earth intermediate is obtained. S2: Under inert gas protection, the macrocyclic Schiff base ligand is added to the organic solution of neodecanoic acid rare earth intermediate obtained in step (1), and heated under reflux to coordinate it; after the reaction is completed, the rare earth ternary complex with neodecanoic acid ion and macrocyclic Schiff base is obtained by concentration, precipitation, filtration, washing and drying.
4. The room temperature vulcanizing oil-resistant and fire-retardant silicone rubber as described in claim 3, characterized in that: At least one of the following conditions must be met: In step S1, rare earth inorganic salts include one or more of rare earth chlorides, rare earth nitrates, and rare earth sulfates. In step S1, the organic solvent includes one or more of toluene, xylene, tetrahydrofuran, n-hexane, cyclohexane, n-heptane, and petroleum ether. In step S1, the molar ratio of rare earth elements to neodecanoic acid is 1.0:2.0~10.0; In step S1, the mass ratio of water to organic solvent is 1:1.5~6.0; In step S1, the pH of the system is controlled to be 6.0~7.5; In step S1, the reaction temperature is 40℃~60℃; In step S1, the reaction is stirred for 2 to 4 hours. In step S2, the molar ratio of rare earth elements to macrocyclic Schiff base ligands is 1.0:(0.5~2.0). In step S2, the pH of the system is controlled to be 6.0~7.5; In step S2, the reaction temperature is 40℃~60℃; In step S2, the reaction is stirred for 2 to 4 hours.
5. The room temperature vulcanizing oil-resistant and fire-retardant silicone rubber as described in claim 2, characterized in that: At least one of the following conditions must be met: In step (1), the alkoxy group in the organic trimekoxysilane includes one or more of the following: methoxy, ethoxy, propoxy, isopropoxy, butoxy, isobutoxy, long-chain alkoxy, and branched-chain alkoxy. In step (1), the mass of the catalyst is 0.01% to 0.1% of the mass of the organotrialkoxysilane, more preferably 0.02% to 0.06%; In step (1), the mass of the mixed solvent is 300% to 1000% of the mass of the organic trialkoxysilane; In step (1), the reaction temperature is 20℃~80℃; In step (1), the reaction time is 1h to 12h; In step (1), the stirring speed is 60 rpm to 600 rpm; In step (1), the absolute pressure during the vacuum distillation process is 1 kPa to 50 kPa.
6. The room temperature vulcanizing oil-resistant and fire-retardant silicone rubber as described in claim 2, characterized in that: At least one of the following conditions must be met: In step (2), the boron-containing compound is one or both of dialkylalkoxyborane and dialkylhydroxyborane; In step (2), the molar ratio of boron atoms in the boron-containing compound to silicon atoms in the organotrialkoxysilane is 1:1 to 1:
20. In step (2), the reaction temperature is 80℃~160℃; In step (2), the reaction time is 2h~12h; In step (2), the stirring speed is 100 rpm to 300 rpm; In step (2), the absolute pressure is 1 kPa to 80 kPa.
7. The room temperature vulcanizing oil-resistant and fire-retardant silicone rubber as described in claim 1, characterized in that: At least one of the following conditions must be met: The hydroxyl-terminated polysiloxane includes one or a mixture of two or more of hydroxyl-terminated polydimethylsiloxane, hydroxyl-terminated polyphenylmethylsiloxane, and hydroxyl-terminated polytrifluoropropylmethylpolysiloxane; The fireproof filler includes one or more of the following: kaolin, attapulgite, mica powder, halloysite, mullite, vermiculite powder, silica fume, aluminum silicate, and diatomaceous earth. The flame retardant includes one or a mixture of two or more of the following: platinum flame retardant, magnesium hydroxide, aluminum hydroxide, melamine, ammonium polyphosphate, melamine cyanurate, melamine pyrophosphate, and zinc borate.
8. The room temperature vulcanizing oil-resistant and fire-retardant silicone rubber as described in claim 1, characterized in that: The hydroxyl-terminated polysiloxanes mentioned above include at least hydroxyl-terminated trifluoropropylmethyl polysiloxane; Preferably, the hydroxyl-terminated polysiloxane contains 10% to 90% by mass of hydroxyl-terminated trifluoropropylmethyl polysiloxane. Preferably, the hydroxyl-terminated trifluoropropylmethyl polysiloxane is a hydroxyl-terminated linear trifluoropropylmethyl polysiloxane.
9. The room temperature vulcanizing oil-resistant and fire-retardant silicone rubber as described in claim 8, characterized in that: The preparation method of the hydroxyl-terminated linear trifluoropropylmethyl polysiloxane includes the following steps: T1: An alkylcyclosiloxane, a fluoroalkylcyclosiloxane, and the catalyst are added to a reaction vessel. The alkylcyclosiloxane is a cyclosiloxane containing a methyl group as a side chain, and the fluoroalkylcyclosiloxane is a cyclosiloxane containing a trifluoropropyl group as a side chain. An inert gas is introduced for protection, and the mixture is heated and stirred under anhydrous conditions. The fluoroalkylcyclosiloxane and the alkylcyclosiloxane undergo a ring-opening copolymerization reaction to form an intermediate product containing a fluoroalkyl polysiloxane. T2: Add a hydroxyl-termining agent to the reaction vessel and continue heating and stirring under anhydrous and inert gas protection. The terminating agent undergoes a condensation reaction with the intermediate product of fluorinated hydrocarbon polysiloxane, thereby terminating chain growth. At the same time, the low-boiling-point byproducts in the reaction system are distilled off under reduced pressure to obtain hydroxyl-terminated linear trifluoropropylmethyl polysiloxane.
10. The room temperature vulcanizing oil-resistant and fire-retardant silicone rubber as described in claim 9, characterized in that: At least one of the following conditions must be met: In step T1, the alkylcyclosiloxane includes one or more of hexamethylcyclotrisiloxane, octamethylcyclotetrasiloxane, decamethylcyclopentasiloxane, and dodecylcyclohexasiloxane. In step T1, some of the methyl groups on the alkylcyclosiloxane are replaced by one or more groups selected from vinyl, phenyl, chlorophenyl, cyanoalkyl, ethyl, propyl, hexyl, octyl, and decyl. In step T1, the fluoroalkyl cyclosiloxane includes one or more of trifluoropropylmethylcyclotrisiloxane, trifluoropropylmethylcyclotetrasiloxane, and trifluoropropylmethylcyclopentasiloxane. In step T1, some of the methyl groups on the fluoroalkyl cyclosiloxane are replaced by one or more groups selected from vinyl, phenyl, chlorophenyl, cyanoalkyl, ethyl, propyl, hexyl, octyl, and decyl. In step T1, the mass of the catalyst accounts for 0.03% to 0.18% of the sum of the masses of the fluoroalkyl cyclosiloxane and the alkyl cyclosiloxane. In step T1, the reaction temperature is 50℃~150℃; In step T1, the reaction time is 1h to 10h; In step T1, the stirring speed is 100 rpm to 600 rpm; In step T2, the hydroxyl-terminated agent includes one or more of hydroxyl silicone oil, vinyl hydroxyl silicone oil, hydroxyl-terminated phenyl silicone oil, and hydroxyl-terminated fluorosilicone oil. In step T2, the molar amount of the hydroxyl end-capping agent is 0.5% to 6% of the sum of the molar amounts of the fluoroalkyl cyclosiloxane and the alkyl cyclosiloxane; In step T2, the reaction temperature is 50℃~120℃; In step T2, the reaction time is 2h~8h; In step T2, the stirring speed is 100 rpm to 600 rpm; In step T2, the absolute pressure is 0.1 kPa to 2.0 kPa.
11. The room temperature vulcanizing oil-resistant and fire-retardant silicone rubber as described in claim 1, characterized in that: Including at least one of the following: diluent, reinforcing agent, structure control agent, crosslinking agent, catalyst, heat resistant agent, and regulator; Preferably, the diluent is 2 to 50 parts, the reinforcing agent is 5 to 100 parts, the crosslinking agent is 0.5 to 10 parts, the catalyst is 0.01 to 3 parts, the heat resistant agent is 0.2 to 10 parts, and the regulator is 0.1 to 5 parts. Preferably, the diluent includes one or a mixture of two or more of methyl silicone oil, hydroxyl silicone oil, hydrogen-containing silicone oil, vinyl silicone oil, phenyl silicone oil, and alkoxy silicone oil. Preferably, the reinforcing agent includes one or more of the following: fumed silica, precipitated silica, silica powder, and nano-calcium carbonate. Preferably, the structuring control agent includes one or more of the following: hydroxyl-terminated polydimethylsiloxane, diphenylsilanediol, dimethyldialkoxysilane, diphenyldialkoxysilane, and hexamethyldisilazane. Preferably, the crosslinking agent includes one or more of the following: polyfunctional alkoxysilanes and siloxanes, acyloxysilanes, ketooxime silanes, allyloxysilanes, amide silanes and siloxanes, and aminooxysilanes and siloxanes. Preferably, the catalyst comprises one or a mixture of two or more of the following: organic amines, ammonium carbamate, potassium acetate, alkali metal hydroxides, organotin compounds, titanates, and guanidine alkoxysilanes. Preferably, the heat resistant agent is one or a mixture of two or more of the following: iron oxide, cerium oxide, magnesium oxide, titanium oxide, zinc oxide, cerium acetate, phenyl-containing polyazo compounds, indole compounds, etc. Preferably, the regulator includes one or a mixture of two or more of cyanoalkoxysilane, liquid polybutadiene, dihydroxypolydimethylsiloxane, and polyether silicone oil.
12. A method for preparing room temperature vulcanizing oil-resistant and fire-retardant silicone rubber according to any one of claims 1 to 11, characterized in that: Each component is added to a kneader and heated and mixed evenly to obtain a compound. The compound is then vulcanized at room temperature. Preferably, the compound is vulcanized at room temperature and relative humidity of 20% to 70%.
13. A fireproof and heat-insulating connector, wherein the substrate connection is vulcanized to obtain the room temperature vulcanizing oil-resistant and fireproof silicone rubber as described in any one of claims 1 to 11.
14. A fireproof and heat-insulating material comprising the room-temperature vulcanizing oil-resistant and fireproof silicone rubber as described in any one of claims 1 to 11.